2017
DOI: 10.1002/adma.201704674
|View full text |Cite
|
Sign up to set email alerts
|

Homoepitaxial Growth of Large‐Scale Highly Organized Transition Metal Dichalcogenide Patterns

Abstract: Controllable growth of highly crystalline transition metal dichalcogenide (TMD) patterns with regular morphology and unique edge structure is highly desired and important for fundamental research and potential applications. Here, single-crystalline MoS flakes are reported with regular trigonal symmetric patterns that can be homoepitaxially grown on MoS monolayer via chemical vapor deposition. The highly organized MoS patterns are rhombohedral (3R)-stacked with the underlying MoS monolayer, and their boundaries… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
105
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 73 publications
(111 citation statements)
references
References 46 publications
6
105
0
Order By: Relevance
“…Hence, a high feeding rate of Se combined with a high growth temperature can offer the synthesis of a large‐scale WSe 2 monolayer with an ultrafast growth rate. Afterward, Loh et al developed a detailed exploration of the morphology evolution by controlling the growth precursor. Here, the Mo supply was in excess during the growth process, which is due to the use of Mo foil as the Mo source.…”
Section: D Semiconducting Tmdsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, a high feeding rate of Se combined with a high growth temperature can offer the synthesis of a large‐scale WSe 2 monolayer with an ultrafast growth rate. Afterward, Loh et al developed a detailed exploration of the morphology evolution by controlling the growth precursor. Here, the Mo supply was in excess during the growth process, which is due to the use of Mo foil as the Mo source.…”
Section: D Semiconducting Tmdsmentioning
confidence: 99%
“…m) An evolution of barrier energy for different edges with respect to µ S . h–m) Reproduced with permission . Copyright 2018, Wiley‐VCH.…”
Section: D Semiconducting Tmdsmentioning
confidence: 99%
“…For instance, the atomically thin feature of 2D materials enables high mechanical flexibility and transparency, which offers an opportunity for flexible and bendable detectors . Their naturally passivated surfaces without dangling bonds make it easy to seamlessly integrate on any substrates . Furthermore, 2D materials can cover a wide‐spectrum range from ultraviolet (UV) to terahertz frequencies (THz, 10 12 Hz) thanks to their multifarious electronic properties .…”
Section: Introductionmentioning
confidence: 99%
“…The key to the success of vdW epitaxy lies in the fact that the surface of 2D TMDC has no dangling bonds, thereby relaxing the lattice matching conditions between the two crystals. Nevertheless, our previous studies have shown that the interlayer vdW interaction between two atomic layers is sufficiently strong to align the grains so that stacking configurations with the lowest energy can be attained, which has implications for the healing of planar defects.…”
Section: Methodsmentioning
confidence: 98%
“…To date, most chemical vapor deposition (CVD) grown films are polycrystalline and contain multiple imperfections, such as point defects, line defects, grain boundaries (GBs), stacking faults, and rotational disorder, which limit the carrier mobility, generate carrier traps, and reduce coherence in light emission. The growth of single phase TMDC films is complicated by the intralayer sliding in each monolayer (resulting in polymorphs, as in 1T and 1H) and interlayer sliding in multilayer films (creating different stacking polytypes, for example, 2H and 3R) . The inherent threefold symmetry as well as fluctuations in chemical potential during growth, coupled with the small energy barriers for rotation and translation of the atomic layers, provides many possibilities for freezing‐in dislocations and stacking faults.…”
Section: Methodsmentioning
confidence: 99%